Apoptotic Dendritic Cells Induce Tolerance in Mice through Suppression of Dendritic Cell Maturation and Induction of Antigen-Specific Regulatory T Cells() - Kushwah, Rahul (J Immunol, 2009)
Dendritic cell (DC) apoptosis has been shown to play a role in maintaining a balance between tolerance and immunity. However, the mechanisms of how DC apoptosis affects the immune response are unclear. We have shown that in vitro culture of apoptotic DCs with immature DCs, results in their uptake by immature DCs, which subsequently turn into tolerogenic DCs, which then secrete TGF-β1 and induce Foxp3(+) regulatory T cells (T(regs)). In this study we looked at the effects of apoptotic DCs in vivo. Here we show that apoptotic DCs are taken up by viable DCs in vivo, which suppresses the ability of viable DCs to undergo maturation and subsequent migration to the lymph nodes in response to LPS. Additionally, delivery of apoptotic DCs to LPS inflamed lungs results in resolution of inflammation, which is mediated by the ability of apoptotic DCs to suppress response of viable DCs to LPS. Additionally, apoptotic DCs also induce TGF-β1 secretion in the mediastinal lymph nodes, which results in expansion of Foxp3(+) T(regs). Most importantly, we show that delivery of apoptotic DCs followed by OVA in CFA to mice suppresses T cell response to OVA and instead induces de novo generation of OVA-specific T(regs). Furthermore, delivery of apoptotic DCs followed by OVA in CFA results in expansion of T(regs) in TCR transgenic (OT-II) mice. These findings demonstrate that apoptotic DCs are taken up by viable DCs in vivo, which promotes tolerance through suppression of DC maturation and induction of T(regs).